Weekly docetaxel and gemcitabine in previously treated metastatic esophageal squamous cell carcinoma - Lee, Min-Young (World J Gastroenterol, 2015)
AIM: To assess the efficacy and safety of weekly docetaxel plus a fixed-dose rate (FDR) of gemcitabine in metastatic esophageal squamous cell carcinoma (SCC). METHODS: A multi-center, open-label, prospective phase II study was designed. Thirty-three esophageal SCC patients with documented progression after fluoropyrimidine/platinum-based first-line chemotherapy were enrolled and treated with docetaxel 35 mg/m(2) and gemcitabine 1000 mg/m(2) iv at a FDR (10 mg/m(2) per minute) on days 1 and 8. Treatment was repeated every twenty-one days until disease progression, unacceptable toxicity, or consent withdrawal. The primary endpoint was response rate (RR), and secondary endpoints were safety, progression-free survival (PFS) and overall survival (OS). RESULTS: Combination of weekly docetaxel and FDR gemcitabine was well tolerated: the most common treatment-related adverse events were anemia (97%), fatigue (64%) and neutropenia (55%). One patient with multiple lung and lymph node metastases died of respiratory failure after receiving four cycles of chemotherapy, and the possibility of drug-induced pneumonitis could not be completely excluded. Disease control (objective response plus stable disease) in the ITT population was achieved in 88% of patients, and the overall RR was 30% (95%CI: 15%-46%). The median PFS and OS were 4.0 (95%CI: 3.4-4.6) and 8.8 mo (95%CI: 7.8-9.8 mo), respectively. CONCLUSION: A combination of weekly docetaxel and FDR gemcitabine showed promising antitumor activity and tolerability in previously treated, metastatic esophageal SCC.